2019
DOI: 10.1177/0733464819847885
|View full text |Cite
|
Sign up to set email alerts
|

Generational Distinctions on the Importance of Age-Friendly Community Features by Older Age Groups

Abstract: In 2006, the World Health Organization initiated an international movement to enhance active aging and the age-friendliness of communities by focusing efforts on the built, social, and service environment. The global model requires soliciting older adults’ preferences regarding community features although findings are typically aggregated across all aged respondents despite mounting distinctions between the generations. This study aimed to examine the differential salience of community features by older genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…After controlling for potentially influential covariates, we found that the health cluster was not a significant factor when estimating self-rated importance of outdoor spaces and buildings. Our findings reinforce previous research that identified younger age as associated with greater utilization of outdoor spaces as we also found older age was associated with lower importance of age-friendly outdoor spaces and buildings [ 25 ]. It should be noted that this finding was consistent after controlling for health and disability-related factors, potentially suggesting cohort differences or other unmeasured factors that should be investigated in the future.…”
Section: Discussionsupporting
confidence: 91%
“…After controlling for potentially influential covariates, we found that the health cluster was not a significant factor when estimating self-rated importance of outdoor spaces and buildings. Our findings reinforce previous research that identified younger age as associated with greater utilization of outdoor spaces as we also found older age was associated with lower importance of age-friendly outdoor spaces and buildings [ 25 ]. It should be noted that this finding was consistent after controlling for health and disability-related factors, potentially suggesting cohort differences or other unmeasured factors that should be investigated in the future.…”
Section: Discussionsupporting
confidence: 91%
“…However, none of the studies focused on advanced-age cohorts such as nonagenarians and centenarians-groups that are significantly increasing in number worldwide. Significant differences were also observed between age groups in relation to preferences concerning AFCC domains, such as use of public transport, outdoor activity, participation in social activities and housing; this is in line with other studies [89]. Eight studies considered gender as an inclusion criterion.…”
Section: Discussion: Study Characteristicssupporting
confidence: 87%
“…For example, research supports our findings that engagement with social opportunities, lifelong learning, having a purpose-in-life, and maintaining a positive attitude are among the most important characteristics of healthy aging (Phelan et al, 2004; Reichstadt et al, 2007, 2010). In addition, Black and Hyer (2020) demonstrate that Baby Boomers in the American Southeast also prioritize accessible city amenities and access to volunteer and employment opportunities as desirable components of healthy aging, which is corroborated by our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Research has indicated that older adults, especially those with lower income, may be more reliant on their physical surroundings (Rowles & Bernard, 2013) and that supportive housing environments can serve a compensating role by providing social and material resources (Ahn et al, 2017; Park et al, 2017). Similar to Black and Hyer’s (2020) study, Anchorage participants recognize that their ability to age at home may be limited, instead expressing a desire for alternative safe and affordable senior housing options that provide a socially integrated environment in the community.…”
Section: Discussionmentioning
confidence: 82%